2012
DOI: 10.1016/j.jmb.2012.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Interaction between Neurotensin Receptor NTS1 and Gq Protein by Lipid

Abstract: Membrane lipids have been implicated to influence the activity of G protein-coupled receptors (GPCRs). Almost all of our knowledge on the role of lipids on GPCR and G protein function comes from work on the visual pigment rhodopsin and its G protein transducin, which reside in a highly specialized membrane environment. Thus insight gained from rhodopsin signaling may not be simply translated to other non-visual GPCRs. Here, we investigated the effect of lipid head group charges on the signal transduction prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
131
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(146 citation statements)
references
References 93 publications
(120 reference statements)
12
131
2
Order By: Relevance
“…As a control, PglC and MSP in the absence of phospholipids did not afford detectable particles, and it is likely that the protein components precipitated under detergent withdrawal conditions. We note that the measured polydispersities are somewhat high, which may indicate the presence of a population of aggregates, which has been documented previously with DLS measurements on nanodisc assemblies (33).…”
Section: Incorporation and Characterization Of Pglc And Pgla In Membranesupporting
confidence: 80%
See 3 more Smart Citations
“…As a control, PglC and MSP in the absence of phospholipids did not afford detectable particles, and it is likely that the protein components precipitated under detergent withdrawal conditions. We note that the measured polydispersities are somewhat high, which may indicate the presence of a population of aggregates, which has been documented previously with DLS measurements on nanodisc assemblies (33).…”
Section: Incorporation and Characterization Of Pglc And Pgla In Membranesupporting
confidence: 80%
“…Undecaprenol was extracted from the leaves of the staghorn sumac (Rhus typhina) and phosphorylated using chemical or enzymatic methods (SI Text). Und-[ 33 P]P was prepared by using Streptococcus mutans kinase and [γ 33 P] ATP (46). UDP-diNAcBac was prepared using a chemoenzymatic approach exploiting PglF, PglE, and PglD of the pgl pathway (47).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction of membrane lipids with these receptors is therefore an important determinant in their structure and function [36,[41][42][43][44]. In addition, it has recently been reported that the interaction between GPCRs and G proteins could be modulated by membrane lipids [45]. Importantly, the membrane lipid environment of GPCRs has been implicated in disease progression during aging [46].…”
Section: Lipid Specificity Of Gpcrsmentioning
confidence: 99%